Initial posting—a critical stage in the employment cycle: lessons from the experience of government doctors in Gujarat, India. Issue 1 (December 2016) - Purohit, Bhaskar; Martineau, Tim
Abstract Background With the critical shortage of government doctors serving in rural health centers in India, understanding the initial posting policies, processes, and practices become important from a retention point of view. The initial posting is a very critical stage of an employment cycle and could play an important role in influencing the key human resource for health outcomes such as turnover and performance. The current study aimed at exploring a rather unknown phenomenon of the initial posting-related processes, practices, and perceptions of Medical Officers working with the Public Health Department in Gujarat, India. Methods This was an exploratory study carried out in the state of Gujarat, India, that used qualitative methods first to document the extant initial posting policy with the help of document review and five Key Informant interviews; next, 19 in-depth interviews were carried out with Medical Officers to assess implementation of policies as well as processes and systems related to the initial posting of Medical Officers. A thematic framework approach was used to analyze qualitative data using NVIVO. Results The results indicate that there is no formal published or written initial posting policy in the state, and in the absence of a written and formal policy, the overall posting systems were perceived to be arbitrary by the study respondents. In the absence of any policy, the state has some unwritten informal practices such as posting the Medical Officers at their native places. Although this practice reflects a concern towards the Medical Officer's needs, such practices are not consistently applied indicating some inequity and possible implications over Medical Officers' retention and motivation. Conclusions Initial posting is a critical aspect of an employment cycle, and the perceptions and experiences of MOs regarding the processes and practices involved in their initial posting can be crucial in influencing their performance and turnover rates. If long-term solutions are to be sought in addressing the availability and distribution of Medical Officers in the state, then there is a need to have clearly laid down initial posting-related policies that reflect the equity and consideration towards Medical Officers in placement-related matters.